The Football Lads Alliance and Democratic Football Lad's Alliance: an insight into the dynamism and diversification of Britain's counter-jihad movement. (3rd September 2019) - Allen, Chris
ABSTRACT: In response to 2017's terror attacks in Britain, the Football Lads Alliance (FLA) and latterly, the Democratic Football Lads Alliance (DFLA) were formed. Self-described as street-protest movements that encourage rival 'football firms' to reject acrimonious hostilities to unite against the Islamist extremism and extremists it believes are threatening Britain, its culture, values and way of life. As new incarnations of the British counter-jihad movement, this article affords new insights into how the movement and constituent parts are dynamically identifying and mobilising behind an increasingly diverse range of identities and socio-political issues. Contributing new knowledge about the FLA and DFLA, neither of which have been subjected to scholarly inquiry, this article makes a timely contribution to an embryonic scholarly canon. Contextualising the counter-jihad movement, this article explores how 'football' afforded the FLA and DFLA with a shared identity around which to mobilise. Highlighting how this is different to other far-right and counter-jihadi groups, their ideologies and activities are explored in relation to their establishment, support base and function. In conclusion, this article positions both groups within an 'identity-oriented' paradigm of new social movements as a means of offering new understanding and explanation.